Training on Bioconversion of Coffee Pulp Waste into Vegan Leather Raw Material in Dusun Krajan, Tegalharjo, Glenmore, Kabupaten Banyuwangi - Ardyati, Tri; Mora, Giral Baines; Permatasari, Dewi; Maulidiyah, Nuris Shobah; Wahyudi, Aleyda Nur Halizah; Srihardyastutie, Arie; Poerwadi, Bambang; Zubaidah, Elok (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Banyuwangi is the largest coffee plantation centre in East Java, with robusta and arabica coffee production reaching 10,518 tonnes per year. Coffee plantation waste, which is abundant, is known as coffee pulp. Coffee pulps can be converted into organic compost/fertilizer, animal feed, and eco-friendly products such as cellulose-based nata/membrane. The abundant availability of coffee pulp waste in Banyuwangi Regency has not been correctly handled or processed to prevent environmental impact. Converting coffee pulp waste into eco-friendly products will benefit the surrounding community and increase the added value of the waste. To overcome these problems, it is necessary to engage in activities involving the local community, local government, and agro-tourism actors through counseling and training on processing coffee pulp waste/bioconversion into eco-friendly products, thereby benefiting the community in Banyuwangi Regency, especially in the Glenmore area. Training participants were given a questionnaire for assessment. Based on the results of the questionnaire analysis, it is known that the participants' understanding before the activity is: 40% of participants were very poorly understood, 13% were poorly understood, 20% were quite understood, 13% understood, and 13% were very familiar with the material of processing coffee pulp waste. After receiving training, 27% of participants achieved an excellent understanding, 33% had a moderate understanding, and 33% had a somewhat understanding. Additionally, there were still participants who did not understand as much as 7%. Based on the participants' assessment, 67% felt that the benefits of this activity were excellent and should be carried out on an ongoing basis.